Processing-properties relationship of nanostructured Ni-Fe-Mo magnetic materials - Shen, Yanping (2008)
The investigation of HEBM Ni-Fe-Mo was to study the properties of nanostructured magnetic materials. Materials used in this experiment were elemental Mo powders and pre-alloyed FeNi3 powders. The results showed that even after 100 h of high energy ball milling, the only detected phase was FeNi3. Mo atoms were substituted into the FeNi3 phase, and destroyed the long-range FeNi3 lattice to form short-range order. Saturation magnetization decreased during the substitution process. However, coercivity was mainly affected by the milling process and was independent of the substitution of Mo.